2019
DOI: 10.21873/invivo.11534
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells as an Indicator and Prognostic Marker in Molecular Subtypes of Breast Cancer

Abstract: Background/Aim: Mast cells (MCs) represent the most controversial non-malignant element of the tumor microenvironment. Our aim was to study how MCs density and distribution (intratumoral-MCit versus peritumoral-MCpt) relate to tumor grade and molecular subtypes. Materials and Methods: MCs tryptase immunohistochemistry was performed on 80 cases of breast carcinomas. Results: For Luminal A tumors, a partial correlation was detected between MCit and progesterone receptor (PR) (p=0.005). Luminal B tumors showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
3
20
1
1
Order By: Relevance
“…[45] Some scholars believe that mast cell infiltration suggests a good prognosis of breast cancer. [46,47] On the other hand, MCs as a proliferating factor, can stimulate the development of breast cancer and is related to the adverse reactions of neoadjuvant chemotherapy for breast cancer, [48,49] which is consistent with the poor prognosis of high expression MCs found in our study. A large number of studies have shown that TIICs has prognostic value independent of many established prognostic signs, and single TIICs have the ability to predict clinical outcomes.…”
Section: Relationship Between Tiic Subsets and Clinical Characteristicssupporting
confidence: 86%
“…[45] Some scholars believe that mast cell infiltration suggests a good prognosis of breast cancer. [46,47] On the other hand, MCs as a proliferating factor, can stimulate the development of breast cancer and is related to the adverse reactions of neoadjuvant chemotherapy for breast cancer, [48,49] which is consistent with the poor prognosis of high expression MCs found in our study. A large number of studies have shown that TIICs has prognostic value independent of many established prognostic signs, and single TIICs have the ability to predict clinical outcomes.…”
Section: Relationship Between Tiic Subsets and Clinical Characteristicssupporting
confidence: 86%
“…The concentrations of SCF, RANTES and SDF1 used were the mean found in all conditioned media (20 pg/mL SCF, 50 pg/mL RANTES, 200 pg/mL SDF1); G-CSF, GM-CSF, MCP1 and IL-8 were used in two different concentrations: the mean found in non-aggressive cells (defined as low concentration), and the mean found in MDA-MB-231 aggressive cells (defined as high concentration). Low concentrations were: 50 pg/mL G-CSF, 50 pg/mL GM-CSF, 500 pg/mL MCP1 and 50 pg/mL IL-8; while high concentrations were: 5 ng/mL G-CSF, 500 pg/mL GM-CSF, 5…”
Section: Migration Assaymentioning
confidence: 95%
“…Mast cells (MCs) are also common components of the breast tumor stroma [2,3,5]. MCs are multifunctional tissue-resident cells of the immune system, that upon activation, and depending on the type of stimuli and receptor involved, release three distinct classes of biologically active compounds:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations